2020
DOI: 10.3103/s0096392520030086
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Proteolytic Enzymes and Their Inhibitors as Perspective Biocides with Antifungal Action

Abstract: Обзор посвящен выявлению групп пептидаз, вовлеченных в процессы роста грибов, а также ингибиторов таких пептидаз. Рассмотрены имеющиеся данные по разнообразию, значимости, представленности и особенностям протеолитических ферментов представителей родов Aspergillus, Penicillium, Trichoderma и Alternaria. На основе анализа данных сделан вывод, что сериновые, металло-и глутаминовые пептидазы необходимы для роста грибов. Поэтому эти ферменты рассматриваются как перспективные мишени ингибиторов пептидаз, что может с… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…It has been previously shown that the efficiency of the use of metal NPs can be increased by combining them with cyclic peptides that exhibit antifungal properties [18]. Unlike peptides that exhibit antimicrobial activity, the enzymes have catalytic activity [19], which allows them not just to trigger destructive processes against fungi but to repeatedly participate in these acts of biocatalysis, deepening antifungal processes. In addition, a wide substrate range of action of the enzymes themselves allows us to consider the possibility of not only their destructive activity against fungal cells but also against the most important fungal molecules involved in the formation of their quorum sensing (QS) and adhesion [20] and molecules that ensure their own safety (antibiotics [21] and mycotoxins [22]).…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously shown that the efficiency of the use of metal NPs can be increased by combining them with cyclic peptides that exhibit antifungal properties [18]. Unlike peptides that exhibit antimicrobial activity, the enzymes have catalytic activity [19], which allows them not just to trigger destructive processes against fungi but to repeatedly participate in these acts of biocatalysis, deepening antifungal processes. In addition, a wide substrate range of action of the enzymes themselves allows us to consider the possibility of not only their destructive activity against fungal cells but also against the most important fungal molecules involved in the formation of their quorum sensing (QS) and adhesion [20] and molecules that ensure their own safety (antibiotics [21] and mycotoxins [22]).…”
Section: Introductionmentioning
confidence: 99%